2021
DOI: 10.1101/2021.02.17.21251953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 associated autoimmunity is a feature of severe respiratory disease - a Bayesian analysis

Abstract: Background: Serological and clinical features with similarities to systemic autoimmunity have been reported in severe COVID-19, but there is a lack of studies that include contemporaneous controls who do not have COVID-19. Methods: Observational cohort study of adult patients admitted to an intensive care unit with acute respiratory failure. Patients were divided into COVID+ and COVID- based on SARS-CoV-2 PCR from nasopharyngeal swabs and/or endotracheal aspirates. No COVID-19 specific interventions were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…In this study, we detected ANA positivity in 40% of patients exhibiting hair loss after COVID-19 infection. This is consistent with previous studies reporting rates ranging from 21% to 64% [15][16][17][18][19][20]. Nevertheless, it is important to note that all COVID-19 patients in those studies had severe or moderate COVID-19, whereas the patients included in our study had mild COVID-19 and did not require hospitalization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we detected ANA positivity in 40% of patients exhibiting hair loss after COVID-19 infection. This is consistent with previous studies reporting rates ranging from 21% to 64% [15][16][17][18][19][20]. Nevertheless, it is important to note that all COVID-19 patients in those studies had severe or moderate COVID-19, whereas the patients included in our study had mild COVID-19 and did not require hospitalization.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, in this study, cytoplasmic ANA patterns were observed in 83.3% of the patients with hair loss after COVID-19 infection. Trachtenberg et al, who reported 64% ANA positivity, found a highly dense and fine-speckled cytoplasmic pattern associated with COVID-19 worsening clinical severity scores [20]. However, as previously noted, all patients with hair loss in our study had mild COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…Our data differ from previous reports suggesting a pathological role of antibodies to lipids. These studies indicate a correlation between the presence of antiphospholipid antibodies (32,(39)(40)(41)(42)(43)(44) and disseminated microthrombi, which have been observed in almost 30% of patients with worsening pneumonia and in some fatal cases (32,33).…”
Section: Discussionmentioning
confidence: 76%
“…Autoantibodies to cardiolipin are induced by SARS-CoV-2 infection, and there was a significant incidence of thrombosis in subjects infected during the initial waves of the pandemic (30)(31)(32)(33).…”
Section: Autoantibodiesmentioning
confidence: 99%